Synthesis, Characterization And Optimization Of Nanocomposite Scaffold Using Poly Lactide/Multi-Walled Carbon Nanotubes - Jelodar, Hassan Adeli (2011)
Poly(L-lactide) (PLLA) scaffolds have been widely used in tissue engineering in order to regenerate the skin, bone, cartilage, ligament and etc. PLLA has the advantages of biodegradability, a controllable degradation rate, good thermal properties and biocompatibility. It can be produced from renewable resources, and it is nontoxic to humans and the environment. However, most of the three dimensional (3D) scaffolds made by PLLA have relatively poor mechanical properties and they are unable to meet the requirements for certain applications.